Hubungan Antara Asupan Protein Dengan Kemampuan Kognitif Pada Remaja Di Sukoharjo, Jawa Tengah - Setiawan, Esha Putriningtyas, Dr. M. Shoim Dasuki, M.Kes (2017)
Background: Nutritional requirement of adolescents is relatively high, since its needed for growth and development, both macro and micro nutrients, especially protein intake that influence cognitive development of children. Currently, prevalence of lack protein intake in Central Java is the highest at the age group of 13-18 years (52, 4%) which will affect the cognitive abilities of adolescents. Objective: To determine correlation of protein intake andcognitive of adolescents in Sukoharjo, Central Java Methods: This research is an analytic observational research with case control design approach by using purposive sampling technique. Samples were 46 adolescents. Data collection was conducted regarding protein intake by using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and data regarding cognitive was taken using Standard Progressive Matrices (SPM) test. Data processing and analysis were performed by using SPSS 20. 0 with Chi-Square test analysis. Results: Resultof Chi-Square p value = 0.039 analysis exhibited correlation of protein intake and cognitive ability. In addition, odds ratio of (OR) 4.29 was obtained, indicating that respondents who get less protein intake had 4.3 times highrisk to have poor cognitive abilities. Conclusion: Presence of correlation of protein intake and cognitive in adolescents of Sukoharjo, Central Java.